Pendekatan Seni dan Budaya Islam (Islamic Art and Culture): Tinjauan Paradigmatif dan Implementatif dalam Pembelajaran PAI dan Budi Pekerti (PAI-BP) - Susanti, Elya; Riadi, Haris; Susanti, Eti (Jurnal Ilmiah Global Education, 2025)
Education is essentially a cultural process that has a significant influence on the survival of humans in carrying out religious, social, and cultural life. In this context, education and arts and culture are two entities that cannot be separated, because they interact and influence each other. Arts and culture have an important role in shaping the identity and personality of individuals and groups of people. Therefore, the ideal education process contains noble cultural wisdom values, in order to realize the development of students' characters holistically through cognitive, affective, and psychomotor aspects. Specifically, the main objective of Islamic Religious Education and Character Education (PAI-BP) is to shape the character and noble morals of students. Because PAI-BP is full of spiritual values ​​and divine aesthetics, an arts and culture-based approach is considered relevant and effective. Through the integration of arts and culture, educators can design a more innovative, creative, and enjoyable learning process, because the learning contains elements of beauty that have educational value